Construction of an artificial consortium of Escherichia coli and cyanobacteria for clean indirect production of volatile platform hydrocarbons from CO2 - Cui, Yixuan; Rasul, Faiz; Jiang, Ying; Zhong, Yuqing; Zhang, Shanfa; Boruta, Tomasz; Riaz, Sadaf; Daroch, Maurycy (Frontiers in Microbiology, 2022)
Ethylene and isoprene are essential platform chemicals necessary to produce polymers and materials. However, their current production methods based on fossil fuels are not very efficient result in significant environmental pollution. For a successful transition more sustainable economic model, producing these key polymeric building blocks from renewable and sustainable resources such as biomass or CO2 is essential. Here, inspired by the symbiotic relationship of natural microbial communities, artificial consortia composed of E. coli strains producing volatile platform chemicals: ethylene and isoprene and two strains of cyanobacteria phototrophically synthesizing and exporting sucrose to feed these heterotrophs were developed. Disaccharide produced by transgenic cyanobacteria was used as a carbon and electron shuttle between the two community components. The E. coli cscB gene responsible for sucrose transport was inserted into two cyanobacterial strains, Thermosynechococcus elongatus PKUAC-SCTE542 and Synechococcus elongatus PCC7942, resulting in a maximal sucrose yield of 0.14 g/L and 0.07 g/L, respectively. These organisms were co-cultured with E. coli BL21 expressing ethylene-forming enzyme or isoprene synthase and successfully synthesized volatile hydrocarbons. Productivity parameters of these co-cultures were higher than respective transgenic cultures of E. coli grown individually at similar sucrose concentrations, highlighting the positive impact of the artificial consortia on the production of these platform chemicals.